2018
DOI: 10.1021/acs.jpcc.8b08693
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Phonon Modes, Optical Constants, and Optical Band Gap in Two-Dimensional ReS2 Films

Abstract: Effects of temperature on the optical properties of large-area ReS2 films (10 layers), which are prepared by chemical vapor deposition, have been investigated by Raman and reflectance spectra. The phonon frequencies of 18 Raman modes red-shift about 3 cm–1 by increasing the temperature from 140 to 320 K. The optical constants (n and k) at a photon energy region of 0.46–6.52 eV are obtained, and the values blue-shift with increasing temperature. Four interband transitions (E p1, E p2, E p3, and E p4) are observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The linearly fitted result indicated that the temperature coefficient was 1.75 × 10 −4 eV/K. This value is lower than those of other TMDs such as ReS 2 48 . Figures 7 and 8 illustrate the peak energy, damping, and normalized intensity of 2.22-and 3.75-eV optical transitions for bilayer PtSe 2 thin film and 1.51-and 3.39-eV optical transitions for multilayer PtSe 2 thin film as a function of temperature.…”
mentioning
confidence: 71%
“…The linearly fitted result indicated that the temperature coefficient was 1.75 × 10 −4 eV/K. This value is lower than those of other TMDs such as ReS 2 48 . Figures 7 and 8 illustrate the peak energy, damping, and normalized intensity of 2.22-and 3.75-eV optical transitions for bilayer PtSe 2 thin film and 1.51-and 3.39-eV optical transitions for multilayer PtSe 2 thin film as a function of temperature.…”
mentioning
confidence: 71%
“…For ReS 2 , unlike the other TMDC systems, the lack of symmetry, intra-mode couplings and the interactions with acoustic modes incite 36 vibrational modes altogether. Keeping apart the 15 infrared active and three zero-frequency modes, the remaining 18 Raman active ones constitute the A g -like and E g -like vibrational modes, originating from the out-of-plane and in-plane vibrations of the Re atoms, respectively [54]. Figures 6(a)-6(c) depict the Raman intensity maps with the associated color scales, after considering the most intense A g -like (149 cm -1 ) peak, having much less sensitivity toward polarization.…”
Section: Experimental Analysis: Synthesis and Characterizationmentioning
confidence: 99%
“…18 Understanding the role that the off-diagonal elements of the permittivity tensor play in driving polariton losses, and propagation can provide significant insights into what additional opportunities they can afford. Notably, several 2D materials offer such low symmetry crystal structures, while still maintaining the potential for exfoliating thin films, such as ReS 2 , which is a triclinic, van der Waals crystal with low-energy phonon modes 167 and the expectation of a series of broad bandwidth resonances in the far-infrared.…”
mentioning
confidence: 99%